Reconstruction of Death Insurance Regulations for Non-Wage Workers and the Sustainability of the Death Social Security Fund - Pratiwi, Retna (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
This journal explores the reconstruction of death insurance regulations for workers who are not wage recipients, aimed at maintaining the sustainability of the death social security fund in Indonesia. The background of this study stems from the challenges faced by non-wage workers in accessing adequate social security benefits, particularly in the event of death, which is a critical aspect of social protection. The objective of the research is to evaluate the current regulatory framework and propose reforms that ensure equitable access and sustainability of the death benefit program for all workers, regardless of their wage status. The study employs a qualitative research method, utilizing legal analysis and case studies to assess the effectiveness of existing regulations and identify gaps that hinder the optimal functioning of the death insurance system. The results indicate significant disparities in the protection provided to wage and non-wage workers, highlighting the need for a more inclusive approach. The proposed regulatory reconstruction emphasizes the importance of expanding coverage, enhancing contributions, and improving the management of the social security fund to ensure long-term sustainability. The conclusions drawn from this research underscore the urgency of regulatory reforms that align with the principles of social justice and financial viability, ensuring that all workers, particularly those who are non-wage recipients, are adequately protected under the death social security program. This study provides a roadmap for policymakers and stakeholders to address the existing challenges and strengthen the social security framework in Indonesia.